Research of frontal structure of the surface layer of the South Atlantic based on the passing observations in November — December 2018 - V.M. Komorin; V.M. Bolshakov; Yu.M. Dikhanov; E.A. Melnik (Ukrainian Antarctic Journal, 2019)
The purpose was identification the oceanic structures of the surface layer, which were crossed by the ship “More Sodruzhestva”, based on observations of temperature and salinity with high resolution, both in time and in space, during the transatlantic cruise in November-December 2018. Furthermore, the aim was to determine the geographical position of these structures, their ranges of variability and spatial gradients of the observed oceanographic characteristics. The research method consisted in a comparative analysis of the information obtained with the help one of the standard measuring systems used for continuous passing observations at the height of the summer of 2018 and information on the same areas obtained in previous years and reflected in the scientific literature. As a result, such oceanic structures as the Bengal Current, the Southern Subtropical Front, the Sub-Antarctic Front, and the zone of its confluence with the Antarctic Polar Front were identified. Spatial gradients characteristic of fronts were 6—10 times greater than gradients in the spaces between fronts. In areas of the transatlantic section in the western hemisphere, ranging in length from one and a half to two thousand nautical miles, there is a very great similarity between the variability of temperature and salinity, which are not physically interconnected. The correlation coefficient between them on one of the segments with a length of 1600 miles was 0.96. An explanation is given for this phenomenon. One of the conclusions is the assumption that this is not a rare event. It should be quite common in large areas of mixing warm, high-salt subtropical waters and much less salty, in cold Antarctic waters. This assumption must be verified. We show a good coincidenceof the results of our contact observations and satellite data.